How Short-Form Travel Videos on TikTok Drive Intention Through Presence, Enjoyment, Flow Experience in Indonesian Gen Z - Achmad Azizan Irdinanto; Muhammad Qaishar Fathin; Nissa Ghulma Ratnasari (Journal of Islamic Economics and Business, 2026)
The growth of Indonesia's tourism industry encourages fierce competition in the fight for the attention of tourists, especially Generation Z, who allocate around 29 percent of their income to tourism activities. This group makes short-form video content on TikTok the main reference in determining travel destinations. This study aims to examine the influence of the quality of tourism short video information, including information usefulness, information ease of use, and information comprehensiveness, on travel intention through the mediating roles of presence, enjoyment, and Flow experience in Generation Z Indonesia. A quantitative approach with a causal design was applied using purposive sampling of 237 respondents of Generation Z TikTok users in Indonesia. Hypothesis testing was carried out through Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis using SmartPLS. The results showed that information ease of use and information comprehensiveness had a significant effect on presence, while information usefulness did not. The three dimensions of information quality have a positive effect on enjoyment, with information ease of use as the strongest predictor. Flow experience was found to be the strongest predictor in forming travel intention, followed by enjoyment and presence. This study concludes that deep psychological involvement while consuming tourism content is the main catalyst for the birth of the intention to visit domestic destinations in Generation Z Indonesia.